2001
DOI: 10.1046/j.1365-3040.2001.00755.x
|View full text |Cite
|
Sign up to set email alerts
|

Abscisic acid introduced into the transpiration stream accumulates in the guard‐cell apoplast and causes stomatal closure

Abstract: Petioles of water-sufficient intactUnlike when leaves are stressed, the guard-cell symplast ABA content did not increase because of ABA infusion ( P = 0·48; 3·0 ± ± ± ± 0·5 versus 4·0 ± ± ± ± 1·2 fg guard-cell-pair ----1 ).However, the guard-cell apoplast ABA content increased linearly ( R 2 = 0·98) from ----0·2 ± ± ± ± 0·5 to 3·1 ± ± ± ± 1·3 fg guard-cellpair ----1 ( ª ª ª ª 3·1 m m m m M ) and was inversely related to leaf conductance ( R 2 = 0·82). Apparently, xylem ABA accumulates in the guard-cell wall as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
35
0
3

Year Published

2006
2006
2023
2023

Publication Types

Select...
4
3
3

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(40 citation statements)
references
References 73 publications
2
35
0
3
Order By: Relevance
“…This confirms the idea that the bulk ABA in a leaf does not necessarily control stomatal aperture. For example, Zhang and Outlaw (2001) showed that stomatal aperture was negatively correlated with the ABA concentration in the apoplast of the guard cells, but not with symplastic ABA.…”
Section: Ethylene-insensitive Plants Have Increased Stomatal Conductancementioning
confidence: 99%
“…This confirms the idea that the bulk ABA in a leaf does not necessarily control stomatal aperture. For example, Zhang and Outlaw (2001) showed that stomatal aperture was negatively correlated with the ABA concentration in the apoplast of the guard cells, but not with symplastic ABA.…”
Section: Ethylene-insensitive Plants Have Increased Stomatal Conductancementioning
confidence: 99%
“…Also, abscisic acid (ABA) secreted by Azospirillum lipoferum alleviate water-stress of maize plants. It has been hypothesized that ABA signals the plant to resist water deficiency by controlling stomata closure to reduce water loss [59]. Another stress type, salinity, hinders crop yield of many plants through ethylene biosynthesis [60] that inhibits root growth.…”
Section: Plant Stress Tolerancementioning
confidence: 99%
“…The decrease of water in the soil promoted the increase of the abscisic acid production in the plant, which acts on the stomatal mechanism, being one of the first symptoms of the plants when they perceive the stress (Zhang and Outlaw, 2001). One of the main functions of the ABA is to promote stomatal closure and to avoid the loss of water by transpiration in plants under water deficiency (Sharp et al, 2004).…”
Section: Concentration Of Abscisic Acidmentioning
confidence: 99%